Efeitos do óleo de peixe sobre o estresse oxidativo, a degeneração dendrítica e a amnésia retrógrada causados por isquemia cerebral global e transitória em ratos : influência do regime de tratamento - Bacarin, Cristiano Correia (2015)
Neurodegeneration and cognitive impairment are the main consequences of the transient, global cerebral ischemia (TGCI). Fish oil (FO) is a rich food source of polyunsaturated fatty acids omega-3, mainly docosahexaenoic acid (DHA), known by the vast biological and neuroprotective activity. The aim of this study was to investigate the biochemical, morphological, and behavioral changes TGCI-induced and the FO effect on these changes. In experiment 1, rats were treated with FO (300 mg/kg DHA, 4 doses, 3 days before and immediately after TGCI), submitted to TGCI and after 24 hours of reperfusion the oxidative stress was evaluated. Furthermore, rats were trained in aversive radial maze (ARM), submitted to TGCI and treated with FO (with the same treatment regimen used for evaluate oxidative stress) for test the antiamnesic effect. In experiment 2, rats were trained in ARM and submitted to TGCI. FO (300 mg/kg of DHA) was administered for 10 days according to the treatment regimens (R). R1 - beginning 4 hours after TGCI; R2 - beginning 8 hours after TGCI; and R3 - beginning 12 hours after TGCI. Retention memory tests were realized by 5 weeks after TGCI. In experiment 3, rats were submitted to TGCI and divided into 5 groups with relation to ischemia/reperfusion (I/R) time. After I/R time, the animals were sacrificed for performing of immunohistochemistry for microtubule-associated protein 2 (MAP2). Subsequently, rats were submitted to TGCI, treated with FO (300 mg/kg of DHA, R1 and R3 of the experiment 2), and immunohistochemistry for MA2 was performed at 14 and 28 days of I/R. In the experiment IV, rats were submitted to TGCI and treated with FO (R1, experiment 2) for analysis of brain lipid profile. TGCI-induced oxidative stress was evaluated by decreased antioxidant enzymes activity and concentration of glutathione and increased protein carbonylation. FO reversed oxidative stress to control level. The same treatment regimen that showed antioxidant effect also demonstrates slight antiamnesic effect (or absent). In behavioral analysis of the experiment 2, R1 treatment with FO totally abolished the memory impairment TGCI-induced. R2 and R3 showed lower antiamnesic effects. TGCI caused dendritic degeneration at 14 days of I/R, well visualized through low MAP2 expression. However, at 28 days of I/R was seen increase in the MAP2 expression compared to 14 days of I/R. FO increased MAP2 expression with R1. Finally, lipid profile analysis showed that ischemia and treatment with FO interfered in the fatty acid balance of the hippocampus, with increase in the concentration of DHA and EPA. This study provides evidence that antioxidant and neuroprotective on dendrites effects of the treatment with OP may contribute to the FO long-term antiamnesic effect seen in this and previous work carried out by us.